Sociodemographic and clinical profile of a population with acute heart failure: MED-ICA cohort (2018)
Objective: To determine the epidemiological characteristics of adults with acute heart failure admitted to a University Hospital. Method: A retrospective, descriptive cohort study conducted by reviewing the medical notes of patients over 18 years-old and admitted between July and December 2015 to a hospital in Medellin, Colombia. Results: The study included 361 patients with acute heart failure, with a mean age of 76 years, and of whom 193 (53.4%) were women. A reduced ejection fraction (LVEF) was observed in 183 (50.6%) patients, 19 (5.2%) with an intermediate LVEF, and 148 (40.9%) with normal LEVF. The pharmacological treatment prior to admission included angiotensin-converting-enzyme (ACE) inhibitors / angiotensin II receptor antagonists (ARA2) in 253 (70%) patients, a beta-blocker in 212 (58.7%), and spironolactone in 92 (25.4%). The main cause of acute heart failure was the presence of tachy-brady-arrhythmias (17.5%), followed by infection (17.2%), and exacerbation of chronic pulmonary disease (16.3%). The clinical classification of the decompensation was Stevenson B in 335 (92.7%) patients, Stevenson C in 20 (5.5%), and Stevenson L in 6 (1.6%). The mean admission time was 6 (4-9) days. There were 30 (8.3%) deaths, 50% due to infections associated with cardiac decompensation and 20% due to acute coronary syndrome. Conclusion: Similarities were found with international studies, but there was a higher mortality mainly linked to infection as a decompensation precipitating factor. The triggering factors and aetiology are presented, which are useful data in clinical practice. There was a high level of comorbidities, and their decompensation had a significant impact on the exacerbation of heart failure. The sub-group with the intermediate ejection fraction had features that require further characterisation. © 2018 Sociedad Colombiana de Cardiología y Cirugía Cardiovascular